A study of girder bridge aesthetics - Ding, C.S. (Construction Research Institute of Malaysia, 2021)
There are numerous research on the constructability concept since its introduction in late 1970. However, there are limited studies to study the constructability concept from the aesthetics point of view. For bridge designs, many researchers and designers commented that aesthetics is an important design consideration. Design that is aesthetically appealing should be one important principle under the big umbrella of the constructability concept. This study ranked different girder bridge design alternatives based on their contribution towards the aesthetics of girder bridge design. Twenty-four (24) consulting engineers and contractors in Sarawak, Malaysia were invited to rate various girder bridge components design alternatives in term of their importance in enhancing the aesthetics of girder bridge design based on 5-point Likert Scale. The collected data was analyzed using Relative Importance Index (RII) method. Based on the results, the design alternatives that contributed the most to the girder bridge aesthetics are V-shaped pier (RII 0.975), New Jersey parapet with steel railing (RII 0.933), and box girder (RII 0.900). The results of the present study can provide guidelines to engineers when designing girder bridges. The new knowledge can be considered together with other constructability principles so that girder bridges designed by engineers are not only constructable but also aesthetically appealing. © 2021, Construction Research Institute of Malaysia. All rights reserved.